Development of the University of the Philippines Mindana Integrated Information Management System (UPMIIMS) comuterized allocation of budget subsystem - Cal, Kenn Gerard P. (2009)
The Budget Office of UP Mindanao has had difficulty in keeping, tacking, manipulation of its records, and the generation of its reports since its founding due to the manual nature of its transactions. Also, due to the growth of the university, it was safe to assume that it would have been increasingly difficult for the UP Mindanao Budget Office to continue with this system. Thus, a computerized transaction scheme must be created. The development of the Computerized Allocation of Budget Subsystem (CABS) automated the manipulation, tracking, and record-keeping of the UP Mindanao Budget Office?s obligation slips. It also automated the generation of Reports of Allotment and Obligation (RAO) and Statements of Allotment and Obligation (SAOB), CABS was designed to ease the processing of obligation slips as well as the generation of RAOs and SAOBs. It does these through a secure and user-friendly Graphical User Interface (GUI) that fronts a meticulously designed program engine which manipulates a database. Aside from the main tasks of record-keeping and report generation, CABS was also designed and implemented to amend budget system data through a similarity secure and user-friendly GUI. All of these transactions enable easier and faster budget data processing without the possibility of human errors